“those terrible songs”: Laura E. Richards’s Ditties and the Education of Boys - Ralph J. Poole (European Journal of American Studies)
Songs—singing and composing—were a staple in Laura Richards’s life. Her mother taught her songs, and she taught them to her own children, who found them “terrible” (Stepping Westward 245) at times, however. I want to pursue the educational and entertaining ideal of teaching songs to children, particularly boys, and speculate about Richards’s pedagogical intentions to enhance gendered notions of behavior and identity through her compositions. My readerly quest is to show that her songs, especially those in her collection The Hottentott and Other Ditties (1939), offer non-hegemonic models and gender-fluid potential for envisioning boyhood.